Azole-Induced Myositis after Combined Lung-Liver Transplantation. (25th March 2022) - Happaerts, Sofie; Wieërs, Michiel; Vander Mijnsbrugge, Ward; Godinas, Laurent; Van Raemdonck, Dirk; Ceulemans, Laurens J.; Vos, Robin; Verleden, Geert M.
Abstract : Lung transplant recipients experience a high rate of invasive pulmonary aspergillosis infections, for which voriconazole is the treatment of choice. We report a patient who developed voriconazole-induced myositis that relapsed after one dose of isavuconazole. Our patient was a 38-year-old man who received a single sequential lung transplantation and liver transplantation because of end-stage cystic fibrosis. He presented to our emergency room with acute pain in both forearms at 3 weeks after voriconazole was initiated for invasive pulmonary aspergillosis infection. Levels of voriconazole were normal during the course of therapy. After stopping voriconazole, the symptoms decreased but relapsed after one dose of isavuconazole. Other causes of muscle pain and inflammation were excluded. Magnetic resonance imaging of both arms showed muscle edema in both arms, including involvement of the fascia, consistent with myositis. There were no signs of necrosis. Isavuconazole was discontinued, and the corticosteroid dose was temporarily increased, with rapid resolution of all complaints. Our patient is the fourth reported case of voriconazole-induced myositis, and the first whose symptoms relapsed after initiating isavuconazole.